Altered endocannabinoid-dynamics in craniopharyngioma patients and their association with HPA-axis disturbances. Issue 2 (1st July 2021) - Auer, Matthias K; Gebert, Dorothea; Biedermann, Sarah V; Bindila, Laura; Stalla, Günter; Reisch, Nicole; Kopczak, Anna; Fuss, Johannes
Abstract : Objective: Patients with craniopharyngioma (CP) frequently suffer from morbid obesity. Endocannabinoids (ECs) are involved in weight gain and rewarding behavior but have not been investigated in this context. Design: Cross-sectional single-center study. Methods: Eighteen patients with CP and 16 age- and sex-matched controls were included. Differences in endocannabinoids (2-arachidonoylglycerol (2-AG) and N-arachidonoylethanolamine (AEA)) and endocannabinoid-like molecules (oleoyl ethanolamide (OEA), palmitoylethanolamide (PEA), and arachidonic acid (AA) were measured at baseline and following endurance exercise. We further explored ECs-dynamics in relation to markers of HPA-axis activity (ACTH, cortisol, copeptin) and hypothalamic damage. Results: Under resting conditions, independent of differences in BMI, 2-AG levels were more than twice as high in CP patients compared to controls. In contrast, 2-AG and OEA level increased in response to exercise in controls but not in CP patients, while AEA levels decreased in controls. As expected, exercise increased ACTH and copeptin levels in controls only. In a mixed model analysis across time and group, HPA measures did not provide additional information for explaining differences in 2-AG levels. However, AEA levels were negatively influenced by ACTH and copeptin levels, while OEA levels were negatively predicted by copeptin levels only. There were no significant differences in endocannabinoids depending on hypothalamic involvement. Conclusion: Patients with CP show signs of a dysregulated endocannabinoid system under resting conditions as well as following exercise in comparison to healthy controls. Increased 2-AG levels under resting conditions and the missing response to physical activity could contribute to the metabolic phenotype of CP patients.